The incidence of urea cycle disorders - Summar, Marshall L.; Kölker, Stefan; Freedenberg, Debra; Le Mons, Cynthia; Haberle, Johannes; Lee, Hye-Seung; Kirmse, Brian (Molecular genetics and metabolism, 2013)
A key question for urea cycle disorders is their incidence. In the United States two UCDs, argininosuccinic synthetase and lyase deficiency, are currently detected by newborn screening. We used newborn screening data on over 6million births and data from the large US and European longitudinal registries to determine how common these conditions are. The incidence for the United States is predicted to be 1 urea cycle disorder patient for every 35,000 births presenting about 113 new patients per year across all age groups.